A lot-sizing model for a multi-state system with deteriorating items, variable production rate and imperfect quality - Adetunji, Olufemi (University of Pretoria, 2022)
Dissertation(MSc Applied Science (Industrial and Systems Engineering))--University of Pretoria, 2022.